2021
DOI: 10.1108/ccij-02-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CSR on nonprofit outcomes: how the choice of corporate partner influences reputation and supportive intentions

Abstract: PurposeWhile research has shown that corporate social responsibility (CSR) can enhance a company's reputation, less is known about the effects of CSR communication on nonprofits. Hence, the current study seeks to understand how corporate reputation, message credibility and message source may impact consumers' attitudinal and behavioral intentions toward nonprofits.Design/methodology/approachA 2 (corporate reputation: low vs high) × 2 (CSR communication source: newspaper blog vs nonprofit blog) between-subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Attitudes towards the organization is a common dependent variable in sport CSR research, particularly when combined with purchase intent or other consumer behaviors [22,26]. These are affective judgments of the organization, and research across disciplines have demonstrated that CSR messages lead to positive affective judgments about the organization communicating about the CSR [22,35,64,66,69]. Thus, we predict that sport fans will similarly view a sport organization positively after reading about its efforts to support sustainability programming.…”
Section: Organizational Attitudesmentioning
confidence: 96%
See 4 more Smart Citations
“…Attitudes towards the organization is a common dependent variable in sport CSR research, particularly when combined with purchase intent or other consumer behaviors [22,26]. These are affective judgments of the organization, and research across disciplines have demonstrated that CSR messages lead to positive affective judgments about the organization communicating about the CSR [22,35,64,66,69]. Thus, we predict that sport fans will similarly view a sport organization positively after reading about its efforts to support sustainability programming.…”
Section: Organizational Attitudesmentioning
confidence: 96%
“…When CSR studies discuss the impact of the CSR program, it is conceptualized as the number of people benefitting from the CSR activity [22,35] or the resulting supportive intentions towards an organization or initiative [31,64]; however, the perceived impact of the CSR may be inherent in the program itself [22], and actually be a predictor of consumer attitudes towards the CSR [57]. Often, the concept of impact is operationalized as other variables such as donation amount [19,57] or commitment and effort toward the program [35,65].…”
Section: Impact Of a Csr Programmentioning
confidence: 99%
See 3 more Smart Citations